Polyploid Induction of Long Bean (Vigna sinensis) Using Colchicine with Different Concentrations - Fitri, Anisa; Afandi, Echa Azkia; Anggun, Septiasri; Yuni Ahda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Long bean (Vigna sinensis) is a plant from the Leguminosae family, which has an important role in the Indonesian economy because it is widely consumed as food. The purpose of this research is to utilize mutation technology in supporting plant breeding to produce superior long bean varieties. The research method carried out was a non-factorial Randomized Group Design (RAK), namely soaking the seeds of long bean plants with colchicine to see the effect of colchicine treatment on chromosomal mutations in long bean plants. The results showed significant differences between colchicine concentrations of 0.02% and 0.03%. At a concentration of 0.02%, the cell nucleus appeared solid red and in the center of the cell, but the number and shape of chromosomes were not clearly visible. This concentration is not optimal for inducing polyploidy. Meanwhile, at a concentration of 0.03%, the chromosomes were more clearly visible than the previous concentration.